Do Newborns Have the Ability to Imitate?. Issue 5 (May 2021) - Slaughter, Virginia
Abstract : Neonatal imitation is widely accepted as fact and cited as evidence of an inborn mirror neuron system that underpins human social behaviour, even though its existence has been debated for decades. The possibility that newborns do not imitate was reinvigorated recently by powerful longitudinal data and novel analyses. Although the evidence is still mixed, recent research progresses the debate by ruling out some long-standing explanations for why the effect might be difficult to detect, by showing that only some research groups observe it, and by revealing indications that the published literature is biased. Further advances will be made with updated testing procedures and reporting standards, and investigation of new research questions such as how infants could learn to imitate. Highlights: Although many assume that newborn infants imitate others, new data and analyses suggest it is not a reliable effect. Meta-analysis of human neonatal imitation studies revealed an overall positive effect which was not moderated by major methodological variations, but did vary by research group. Future studies of newborn imitation should adopt modern procedures to eliminate potential biases. Researchers should also test models of how imitation could be learned. Associative Sequence Learning proposes that coincident experience of producing and perceiving body gestures over the first year of life, creates mirror systems to support imitation.